Use of the relaxation technique as a research object: an account of an experiment with adolescentes - Leila Memória Paiva Moraes; Violante Augusta Batista Braga (Rev Rene)
The study intends to describe the experiment of using relaxation in the data production on research carried out on a group of adolescents in a public shelter in Fortaleza-Ce, working on the topic “drugs”. Experiential workshops were conducted, inspired on sociopoetics through the research group, which predicts the use of relaxation as a way of working the research subjects’ imagination and creativity. The methodology employed has proved to be valid and has shown positive results, even if it evinced achievements, advances and drawbacks. With the employment of relaxation the participants became less anxious, creative and involved with the study, which shows that this is an important instrument in the data production. The richness of subsequent moments has been favored by such instrument, creating a space to expressing feelings and experiences related to the way that they deal with drugs.